2022
DOI: 10.31234/osf.io/hq7v9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tearing apart the “evil” twins: A general conspiracy mentality is not the same as specific conspiracy beliefs

Abstract: Although sometimes used interchangeably, the present review highlights the important differences between generalized worldviews suspecting conspiracy at play (conspiracy mentality) and specific beliefs about the existence of a certain conspiracy (conspiracy theory). In contrast to measures of beliefs in specific conspiracy theories, those of conspiracy mentality are more stable, less malleable, less skewed in their distribution and less contaminated by other ideological content. These differences have importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Instead, studies reveal a spectrum of conspiracy susceptibility present among ordinary, non-pathological individuals. 493 2. There is a striking resemblance between a substantial portion of our entertainment and conspiracy theories.…”
Section: What Is Typical For Misinformation?mentioning
confidence: 99%
“…Instead, studies reveal a spectrum of conspiracy susceptibility present among ordinary, non-pathological individuals. 493 2. There is a striking resemblance between a substantial portion of our entertainment and conspiracy theories.…”
Section: What Is Typical For Misinformation?mentioning
confidence: 99%
“…Surveys have shown that the adoption of conspiracy belief is indeed more prevalent in (epistemically) disadvantaged communities. This can be due to being economically or ethnically marginalized (Crocker et al, 1999;Goertzel, 1994;Imhoff, 2015;Imhoff et al, 2022;Parsons et al, 1999;van Prooijen, Staman, et al, 2018), but can have other causes as well.…”
Section: Epistemic Progress and Epistemic Exclusionmentioning
confidence: 99%
“…This is perhaps understandable given the hard-to-reach target population (Franks et al, 2017), but the increasing adoption of web experiments in the field provides a viable alternative (Frenken & Imhoff, 2022a, 2022bGeorgiou et al, 2021c;Meuer & Imhoff, 2021). There is a large literature attempting to characterize the cognitive processing profile of conspiracists using questionnaires (Biddlestone et al, 2022;Bruder et al, 2013;Crocker et al, 1999;Frenken & Imhoff, 2021;Georgiou et al, 2019Georgiou et al, , 2021cHornsey et al, 2022;Imhoff, 2015;Imhoff & Bruder, 2014), yet the information-seeking and metacognition tasks recently developed in typical participants still await to be applied with conspiracists. For example, questionnaire-based research suggests overconfidence, in the form of the illusion of explanatory depth, is prevalent among conspiracists (Vitriol & Marsh, 2018).…”
Section: Metacognition and Information-seeking Tasks In The Labmentioning
confidence: 99%